Which expression represents y to the 4th power -36 in simplest factored form?
Answer
5 (1 оценка)
0
Intriguing456 7 months ago
Светило науки - 96 ответа - 0 помощи

Answer:

(y^2 + 6)(y^2 - 6)

Step-by-step explanation:

First, substite variable x for y^2:

FOR x = y^2:

y^4 - 36

= (y^2)(y^2) - 36

= (x)(x) - 36

= x^2 - 36

Now, use the formula a^2 - b^2 = (a + b)(a - b):

x^2 - 36

= x^2 - 6^2

= (x + 6)(x - 6)

Finally, since the expression is factored for x, not y, substite y^2 in for x:

(x + 6)(x - 6)

= (y^2 + 6)(y^2 - 6)

Still have questions?